Autism friendly library - Jailani, Fatiany Abdul Kader; Mohamad Yunus, Noor'ain; Mat Ali, Syukrina Alini; Mohd Hassan, Naffisah; Ma'on, Siti Noorsuriani; Kassim, Erne Suzila; Mohd Fauzi, Mohamed Fadzli (Universiti Teknologi MARA, Kedah, 2019)
Autism Spectrum Disorder (ASD) is one of the fastest growing disorders and it is estimated that approximately 9000 children in Malaysia are born with ASD every year. According to recent statistics, there are 300,000 individuals living with ASD in Malaysia. However, the growing number Autistic individual is not in tandem with the resources, facilities and program to cater the needs of these community. Previous study revealed that 90% people with Autism and their caregivers willing to visit libraries if some changes were made such as not been judged and practice few simple adaptations for sensory sensitivities example; lightings, noise and crowds. With all the above consideration, the idea of Autism Friendly Library is proposed in order to provide a comfortable library experience to Autistic individual as well as their families. Every Tuesday will be declared as Autism Friendly Library where the environment such as dimmed lights, reduce activities and noise to ensure that autistic children and their families are more comfortable. Some of the proposed features that will be included in the library are private space or calm room, sensory wall, and Autism friendly session. Autism Friendly Library concept provide inclusive library experience that are suitable to meet the needs of the community as well as children with Autism at the same time increasing public understanding and acceptance of Autism Spectrum Disorder (ASD). It is crucial that government and individuals respond in a way that protects the dignity and well-being of Autism community and creates an environment that empowers these community to maximize their potential.